Differential regulation of TNF-α and IL-1β production from endotoxin stimulated human monocytes by phosphodiesterase inhibitors - K. L. Molnar-Kimber; L. Yonno; R. J. Heaslip; B. M. Weichman (Mediators of Inflammation)
The effect of selective PDE-I (vinpocetine), PDE-III (milrinone, CI-930), PDE-IV (rolipram, nitroquazone), and PDE-V (zaprinast) isozyme inhibitors on TNF-α and IL-1β production from LPS stimulated human monocytes was investigated. The PDE-IV inhibitors caused a concentration dependent inhibition of TNF-α production, but only partially inhibited IL-1β at high concentrations. High concentrations of the PDE-III inhibitors weakly inhibited TNF-α, but had no effect on IL-1β production. PDE-V inhibition was associated with an augmentation of cytokine secretion. Studies with combinations of PDE isozyme inhibitors indicated that PDE-III and PDE-V inhibitors modulate rolipram's suppression of TNF production in an additive manner. These data confirm that TNF-α and IL-1β production from LPS stimulated human monocytes are differentially regulated, and suggest that PDE-IV inhibitors have the potential to suppress TNF levels in man.